Anticancer Hybrids- A Patent Survey - Nepali, Kunal; Sharma, Sahil; Kumar, Dinesh; Budhiraja, Abhishek; L. Dhar, Kanaya (Recent Patents on Anti-Cancer Drug Discovery, 2014)
The molecular hybridization (MH) is a strategy of rational design of such ligands or prototypes based on the recognition of pharmacophoric sub-units in the molecular structure of two or more known bioactive derivatives which, through the adequate fusion of these sub-units, lead to the design of new hybrid architectures that maintain pre-selected characteristics of the original templates. The concept of molecular hybridization and the promises/challenges associated with these hybrid molecules along with recent advances on anticancer hybrids and critical discussions on the future aspects of the hybrid drugs have already been presented through a number of reports. However, this article presents the structures of potent hybrids reported during the last two decades along with a detailed account of the patent literature. Significant number of patents on the molecules designed through this valuable drug design technique clearly highlight the present focus of the researchers all around the globe towards hybrid molecules capable of amplifying the effect of individual functionalities through action on another bio target or to interact with multiple targets as one single molecule lowering the risk of drug-drug interactions and minimizing the drug resistance. This review article basically emphasizes the patent literature along with an overview of potent hybrid structures, their IC50 /GI50 values against the various cell lines employed. The present compilation can be utilized as a guide for the medicinal chemists focusing on this area of drug design.
Keywords: microtubule